2021
DOI: 10.3390/atmos12060732
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Modeling of OH and HO2 Radical Concentrations during Toluene and Xylene Oxidation with RACM2 Using MCM/GECKO-A

Abstract: Due to their major role in atmospheric chemistry and secondary pollutant formation such as ozone or secondary organic aerosols, an accurate representation of OH and HO2 (HOX) radicals in air quality models is essential. Air quality models use simplified mechanisms to represent atmospheric chemistry and interactions between HOX and organic compounds. In this work, HOX concentrations during the oxidation of toluene and xylene within the Regional Atmospheric Chemistry Mechanism (RACM2) are improved using a determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We then grouped these products into extremely low volatility (saturation concentration (C*) ≤ 3 × 10 −4 μg m −3 ), low volatility (3 × 10 −4 < C* ≤ 0.3 μg m −3 ), semivolatile (0.3 < C* ≤ 300 μg m −3 ), intermediate volatility (300 < C* ≤ 3 × 10 6 μg m −3 ), and volatile (C* > 3 × 10 6 μg m −3 ) categories as shown in Figure S6 of Supporting Information . Based on the volatility distribution of toluene SOA, we found that semivolatile organic compounds (SVOCs) contributed about 49.6% of total SOA mass concentration (TS2‐3), which is slightly lower than observed fractions (62%–71%) for toluene SOA produced in an oxidation flow reactor (OFR) with a comparable initial toluene condition but lower temperature (Lannuque et al., 2023). This difference might be attributed to differences in initial toluene concentrations, experimental temperature, and speciation variation among toluene oxidation products generated under different reaction durations between OFR and chambers.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We then grouped these products into extremely low volatility (saturation concentration (C*) ≤ 3 × 10 −4 μg m −3 ), low volatility (3 × 10 −4 < C* ≤ 0.3 μg m −3 ), semivolatile (0.3 < C* ≤ 300 μg m −3 ), intermediate volatility (300 < C* ≤ 3 × 10 6 μg m −3 ), and volatile (C* > 3 × 10 6 μg m −3 ) categories as shown in Figure S6 of Supporting Information . Based on the volatility distribution of toluene SOA, we found that semivolatile organic compounds (SVOCs) contributed about 49.6% of total SOA mass concentration (TS2‐3), which is slightly lower than observed fractions (62%–71%) for toluene SOA produced in an oxidation flow reactor (OFR) with a comparable initial toluene condition but lower temperature (Lannuque et al., 2023). This difference might be attributed to differences in initial toluene concentrations, experimental temperature, and speciation variation among toluene oxidation products generated under different reaction durations between OFR and chambers.…”
Section: Resultsmentioning
confidence: 92%
“…Lannuque et al. (2023) found that MCM overestimated gaseous products with high carbon numbers (C 7 ) and their oxidation state compared to gas‐ and particle‐phase products detected in toluene SOA experiments. Consequently, the contribution of C 7 products to toluene SOA was overpredicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many laboratory studies have investigated the oxidation mechanism of toluene to understand the different chemical pathways leading to SOA formation. [34][35][36][37][38][39][40] Lannuque et al 39 built a detailed mechanism for toluene oxidation based on MCM and GECKO-A, which follows recent literature to improve cresol formation, 41 accounts for ring-scission chemistry 34 and the formation of Highly Oxygenated Molecules (HOMs) by autoxidation. 35 However, this mechanism did not consider the molecular rearrangement of bicyclic peroxy radicals (BPRs), which was recently pointed out as a potential key pathway to form SOAs.…”
Section: Introductionmentioning
confidence: 99%
“…35 However, this mechanism did not consider the molecular rearrangement of bicyclic peroxy radicals (BPRs), which was recently pointed out as a potential key pathway to form SOAs. 40 In order to investigate the inuence of different chemical pathways on SOA formation, GENOA is used here to generate condensed toluene SOA mechanisms from MCM and from Lannuque et al 39 These reduced chemical mechanisms are implemented in the aerosol model SSH-aerosol, 42 coupled to the 3D regional and street air-quality models Polair3D 43 and MUNICH. 44 Aer a description of the toluene mechanisms and their reduction, the inuence of the reduced chemical mechanisms on toluene SOA concentrations and composition at urban and street scales is investigated in this study.…”
Section: Introductionmentioning
confidence: 99%